Twin Roll Casting and Strip Rolling of Several Magnesium Alloys. (2015) - Neh, K.; Ullmann, M.; Oswald, M.; Berge, F.; Kawalla, R.
Abstract: The twin roll casting (TRC) process enables the production of magnesium strips in an economic way. In combination with strip rolling, magnesium flat products with a great potential for industrial applications are produced. Current achievable mechanical properties of strips made of several magnesium alloys, produced by twin roll casting and subsequent strip rolling, are shown in this work. Therefore, commercial magnesium alloys AZ31 and AM50 as well as rare earth containing magnesium alloys ZE10, ME21 and WE43, which are known as high strength alloys with good corrosion behavior and creep properties[1], and AZ31 with the addition of silicon carbide are investigated. Initial rolling tests demonstrate, that thin sheets with moderate up to excellent mechanical properties, depending on the alloy composition, can be produced. Especially AZ31 with SiC and WE43 offer high strength and a good elongation.